Boosting Blood Flow: How Warm Compress Helps Manage Blood Pressure in Type 2 Diabetes - Wardika, Izdihar Javier; Widayati, Nur; Ridla, Akhmad Zainur; Setiawan, Iwan (Jurnal Kegawatdaruratan Medis Indonesia, 2025)
Patients with diabetes can affect cardiac output, such as blood pressure dysfunction. Changes in insulin resistance and hyperglycemia can lead to blood pressure dysfunction and increased cardiac output problems. Warm compresses affect macrovascular function and impact blood pressure in patients. This study analyzed the effectiveness of warm compresses in reducing blood pressure in type 2 DM patients with decreased cardiac output problems. The study used a case report method. Warm compresses were applied for three days, for 2 hours per day, using a warm water sack placed on the abdomen at 40-42°C. Blood pressure was measured before and after the intervention. Results showed that after 3 days, there was a reduction in blood pressure, with an average decrease of 16.667 mmHg in systolic and 6.667 mmHg in diastolic pressure. Warm compresses effectively reduce blood pressure in patients with cardiac output problems. Nurses can apply warm compress therapy as a simple intervention to improve blood pressure in patients with decreased cardiac output.